Subjective Well-Being, Test Anxiety, Academic Achievement: Testing for Reciprocal Effects - Steinmayr, Ricarda; Crede, Julia; McElvany, Nele; Wirthwein, Linda (Frontiers in Psychology, 2016)
In the context of adolescents’ subjective well-being (SWB), research has recently focused on a number of different school variables. The direction of the relationships between adolescents’ SWB, academic achievement, and test anxiety is however still open although reciprocal causation has been hypothesized. The present study set out to investigate to what extent SWB, academic achievement, and test anxiety influence each other over time. A sample of N = 290 11th grade students (n = 138 female; age: M = 16.54 years, SD = 0.57) completed measures of SWB and test anxiety in the time span of one year. Grade Point Average (GPA) indicated students’ academic achievement. We analyzed the reciprocal relations using cross-lagged structural equation modeling. The model fit was satisfactory for all computed models. Results indicated that the worry component of test anxiety negatively and GPA positively predicted changes in the cognitive component of SWB (life satisfaction). Worry also negatively predicted changes in the affective component of SWB. Moreover, worry negatively predicted changes in students’ GPA. Directions for future research and the differential predictive influences of academic achievement and test anxiety on adolescents’ SWB are discussed with regard to potential underlying processes.